(untitled) (Fiep Bulletin - online, 2015)
Childhood obesity has been spreading increasingly in recent decades, this is due to increased technology and sedentary lifestyle, their appearance at this age becomes a disturbing fact because the disease can remain throughout adulthood and trigger other problems health diminishing the quality of life of individuals. Therefore the aim of this study was to analyze the level of physical activity and obesity in children, elementary school students from the city of Quatiguá-PR. For data collection anthropometric measures of body mass and height in order to get the BMI of students, and also measures of waist and hip circumference in order to establish the WHR were measured; the Baecke questionnaire was used to assess levels of physical activity among individuals. For statistical analysis was used software BioStat 5.4, adopting the standard of significance at p ? 0.05. The results showed that in this population divided according to ensalamento was no significant difference between the rooms of chronological age, height and body mass. Ever, with respect to the Baecke questionnaire revealed significant differences in the values of work and leisure index, confirming the overall outcome of the survey, which also showed significant differences between the different school years. It is possible to conclude that the students studied did not show in his paintings most worrying in relation to obesity beyond levels of leisure time physical activity were more significant compared to the other items.